SUFFERED, ALIENATED AND DEATH: REPRESENTATION OF HIV/AIDS IN FILM â€œMIKAâ€ (2013) - Faisal, Mochamad (ROLLING, 2024)
Films are often used as a medium to address ongoing issues in society, one of the examples is HIV/AIDS. A â€œdeath sentenceâ€ as results from â€œdeviant behaviorâ€ is still stigmatized and remains a major obstacle in mitigating the spread of the HIV up to the present day, since its first case in Indonesia back in 1987. One of Indonesian films that address the issue of HIV/AIDS is "Mika" (2013) revolves around a girl named Indi who falls in love with Mika, an ex-injectable drug user who suffers and eventually dies from AIDS. This film will be studied from an interdisciplinary perspective by analyzing the content, concepts, and contexts within the framework of visual cultural theories, using descriptive qualitative research methodology. The film "Mika" (2013) should have a close connection to the issues they represent and how they responsibly address the main issue at hand, which is to break the negative stigma associated with HIV/AIDS rather than reinforcing the notion of 'punishment' for 'deviant behavior' by exploiting the tragedy. Keywords: Film, HIV/AIDS, Content, Concept, Context.